2007
DOI: 10.1080/09500690701494084
|View full text |Cite
|
Sign up to set email alerts
|

School Site to Museum Floor: How informal science institutions work with schools

Abstract: Nutzungsbedingungen AbstractTwo research studies sponsored by CILS investigated the programmes ISIs currently provide to support K-12 science education, particularly in the area of teacher professional development (PD). The first study was a large-scale survey with 475 ISIs responding about the programmes they offer schools and teachers beyond one-day field trips. A large majority of ISIs (73%) reported having one or more of these programmes, with more than half (59%) providing one or more forms of teacher PD.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(32 citation statements)
references
References 12 publications
0
31
0
Order By: Relevance
“…Phillips, Finkelstein, and Wever-Frerichs (2007) argue that this fusion may blur the quality of learning outside the classroom. As long as 15 years ago, Griffin and Symington (1997) were already arguing for a move from task oriented to learner oriented strategies for field trips.…”
Section: Social Interactionmentioning
confidence: 99%
See 2 more Smart Citations
“…Phillips, Finkelstein, and Wever-Frerichs (2007) argue that this fusion may blur the quality of learning outside the classroom. As long as 15 years ago, Griffin and Symington (1997) were already arguing for a move from task oriented to learner oriented strategies for field trips.…”
Section: Social Interactionmentioning
confidence: 99%
“…These experiences-with an array of real-life settings, animals, professional science communities, objects, scientific instrumentation, and current research and data-have been shown to spark curiosity, generate questions, and lead to a depth of understanding and commitment in ways that are often less possible when the same material is encountered in books or on screens. ' (Bevan et al, 2010, p. 11) However many LOtC institution, and botanic gardens in particular, do not engage in larger educational reform efforts or in systematic programme evaluation (Phillips et al, 2007) and they often fail to institutionalize collaborations with schools or the educational system. The reasons for this state of affairs are manifold and are often related to the hybrid nature of these collaborations which are both formal and informal at the same time (Bevan et al, 2010).…”
Section: Collaborative Learning At Botanic Gardensmentioning
confidence: 99%
See 1 more Smart Citation
“…If these are to develop worthwhile educational programmes, they should also draw on the work being done in the Social and Experimental Sciences. The approach to heritage in these various contexts takes widely different perspectives in terms of conceptualisation, ends, contents and methodological approaches to teaching and dissemination in both formal and informal education (Fontal, 2003;Martin, 2004;Phillips, Finkelstein, & Wever-Frerichs, 2007). This paper aims to provide a broad picture of the representations that teachers and heritage administrators have of heritage, its teaching and dissemination, and how the initial training each receives might influence their subsequent professional development in this respect.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies suggest, however, that these research efforts are not effectively informing teacher practice within the museum setting (Anderson, Kisiel, & Storksdieck, 2006;DeWitt & Storksdieck, 2008;Griffin & Symington, 1997;Kisiel, 2005Kisiel, , 2007Storksdieck et al, 2005). Furthermore, recent studies suggest that science museum resources are generally underused by the teachers they hope to serve (Bevan, 2007;Finkelstein, 2005;Phillips, Finkelstein, & Wever-Frerichs, 2007) and that external factors such as rising costs and accountability concerns are likely influencing teacher and school participation (Anderson et al, 2006;DeWitt & Storksdieck, 2008).…”
Section: Introduction the Possibilities Of Collaboration Between Schomentioning
confidence: 99%